2021
DOI: 10.3389/fnins.2021.649910
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Nerve Control of Cerebral Blood Flow: A Brief Review

Abstract: The trigeminal nerve, the fifth cranial nerve, is known to innervate much of the cerebral arterial vasculature and significantly contributes to the control of cerebrovascular tone in both healthy and diseased states. Previous studies have demonstrated that stimulation of the trigeminal nerve (TNS) increases cerebral blood flow (CBF) via antidromic, trigemino-parasympathetic, and other central pathways. Despite some previous reports on the role of the trigeminal nerve and its control of CBF, there are only a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 91 publications
(119 reference statements)
0
15
0
Order By: Relevance
“…[51][52][53] Our results are consistent with previous findings that intravascular CGRP dilates small parenchymal vessels, 54,55 and the increase in CGRP is associated with a decrease in ICAM-1 expression. 56 However, it may be also mediated by other vasoactive agents because the free nerve endings of the trigeminal system are known to release a host of vasoactive agents, 16 such as nitric oxide, 57,58 pituitary adenylate cyclase-activating polypeptide, 59,60 and epoxyeicosatrienoic acids, 61,62 which interact directly with endothelial cells to reduce inflammation, reactive oxidative species-mediated damage, and alter the thrombogenicity profile of vascular endothelium. It is our opinion that TNS may much more effectively enhance cerebral microcirculation compared with the administration of a single vasoactive peptide, such as CGRP, by generating a myriad of vasoactive agents targeting different pathological mechanisms of DCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51][52][53] Our results are consistent with previous findings that intravascular CGRP dilates small parenchymal vessels, 54,55 and the increase in CGRP is associated with a decrease in ICAM-1 expression. 56 However, it may be also mediated by other vasoactive agents because the free nerve endings of the trigeminal system are known to release a host of vasoactive agents, 16 such as nitric oxide, 57,58 pituitary adenylate cyclase-activating polypeptide, 59,60 and epoxyeicosatrienoic acids, 61,62 which interact directly with endothelial cells to reduce inflammation, reactive oxidative species-mediated damage, and alter the thrombogenicity profile of vascular endothelium. It is our opinion that TNS may much more effectively enhance cerebral microcirculation compared with the administration of a single vasoactive peptide, such as CGRP, by generating a myriad of vasoactive agents targeting different pathological mechanisms of DCI.…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation, the trigeminal nerve modulates cerebral blood flow (CBF) and produces profound vasodilation by releasing a host of vasoactive agents, such as calcitonin gene-related peptide (CGRP). 16 Prior research has demonstrated that trigeminal nerve stimulation (TNS) can alleviate dysregulation of CBF and resolve large artery cerebral vasospasm (CV) after experimental SAH. [17][18][19] However, whether TNS can improve cerebral microcirculation, mitigate DCI, and improve neurological outcomes has yet to be investigated.…”
mentioning
confidence: 99%
“…In the brain, the principal contributor is trigeminal sensory afferent activation, which directly releases stored CGRP from trigeminal sensory afferent nerve endings into the surrounding tissue. [38][39][40] Conversely, the increase in CGRP levels in the kidney and lung may stem from peripheral nerve exocytosis of CGRP mediated by intermittent hypoxia-and ischemia-induced acidosis. [41][42][43][44][45] While trigeminal activation leads to systemic CGRP elevation, as evidenced by an ~2-3X increases in jugular CGRP levels during cluster headache attacks, 46 the extent to which it affects peripheral organs remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is widely recognized that trigeminal activation releases various other antioxidative neuropeptides in addition to CGRP. 40,70 These neuropeptides could potentially influence NRF2 signaling and serve as underlying factors contributing to the effects of DR. 40,70 Thirdly, the pathways affecting oxidative stress are complex. In this study, we only focused on the NRF2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The role of acute hypertension was discussed as a probable cause, as this has been seen with drug use (cocaine, amphetamines) and cold weather. Trigeminal nerve stimulation also increases cerebral blood flow and can elevate blood pressure 4. Fatal intracerebral hemorrhages (ICHs) have been reported as a consequence of radiofrequency trigeminal lesioning.…”
Section: Discussionmentioning
confidence: 99%